Ruthenium complexes containing 2-(2-nitrosoaryl)pyridine : structural, spectroscopic and theoretical studies - Chan, Siu-Chung (2015)
Ruthenium complexes containing 2-(2-nitrosoaryl)pyridine (ON∧N) and tetradentate thioether 1,4,8,11-tetrathiacyclotetradecane ([14]aneS4), [Ru(ON∧N)([14]aneS4)]2+ [ON∧N = 2-(2-nitrosophenyl)pyridine (2a), 10-nitrosobenzo[h]quinoline (2b), 2-(2-nitroso-4-methylphenyl)pyridine, (2c), 2-(2-nitrosophenyl)-5-(trifluoromethyl)pyridine (2d)] and analogues with the 1,4,7-trithiacyclononane ([9]aneS3)/tert-butylisocyanide ligand set, [Ru(ON∧N)([9]aneS3)(C≡NtBu)]2+ (4a and 4b), have been prepared by insertion of a nitrosonium ion (NO+) into the Ru–aryl bond of cyclometalated ruthenium(II) complexes. The molecular structures of the ON∧N-ligated complexes 2a and 2b reveal that (i) the ON∧N ligands behave as bidentate chelates via the two N atoms and the bite angles are 86.84(18)–87.83(16)° and (ii) the Ru–NNO and N–O distances are 1.942(5)–1.948(4) and 1.235(6)–1.244(5) Å, respectively. The Ru–NNO and N–O distances, together with νN═O, suggest that the coordinated ON∧N ligands in this work are neutral moiety (ArNO)0 rather than monoanionic radical (ArNO)•– or dianion (ArNO)2– species. The nitrosated complexes 2a–2d show moderately intense absorptions centered at 463–484 nm [εmax = (5–6) × 103 dm3 mol–1 cm–1] and a clearly discriminable absorption shoulder around 620 nm (εmax = (6−9) × 102 dm3 mol–1 cm–1), which tails up to 800 nm. These visible absorptions are assigned as a mixing of d(Ru) → ON∧N metal-to-ligand charge-transfer and ON∧N intraligand transitions on the basis of time-dependent density functional theory (TD-DFT) calculations. The first reduction couples of the nitrosated complexes range from −0.53 to −0.62 V vs Cp2Fe+/0, which are 1.1–1.2 V less negative than that for [Ru(bpy)([14]aneS4)]2+ (bpy = 2,2′-bipyridine). Both electrochemical data and DFT calculations suggest that the lowest unoccupied molecular orbitals of the nitrosated complexes are ON∧N-centered. Natural population analysis shows that the amount of positive charge on the Ru centers and the [Ru([14]aneS4)] moieties in 2a and 2b is larger than that in [Ru(bpy)([14]aneS4)]2+. According to the results of the structural, spectroscopic, electrochemical, and theoretical investigations, the ON∧N ligands in this work have considerable π-acidic character and behave as better electron acceptors than bpy.